Perspektif Teologis Terhadap Eskatologi Berdasarkan Kitab Wahyu - Dedi Surianto Laia; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The theological perspective on eschatology in the Book of Revelation includes various views and interpretations that have been submitted by the theologian, preacher, and religious scholars. The Book of Revelation, also known as the Book of Revelation to John, is one of the books in the New Testament in the Christian Bible. It focuses on the vision of the Prophet John who talks about the future and the end of time. Over time, the interpretation differs to the phenomenon of eschatology has sprung up. Although the Bible provides an idea of what will happen at the end of time, the more difficult to interpret how these events will occur in the modern world that continues to grow. Christian understanding of the end of time has developed and changed over time and in different cultural contexts. Therefore, this article will discuss what is the end of time (eschatology). How did the book Revelation talk about eschatology? What is the final picture of the time in the book of Revelation?